Construction control of cable-stayed bridge top push method based on BIM technology - Chen, Chengyong; Su, Wenming; Dou, Wenqiang; Dong, Yongquan; Zhang, Ben (Discover applied sciences, 2025)
This research focuses on enhancing the precision and management of the top push method in cable-stayed bridge construction through the application of building information modeling (BIM) technology. By evaluating BIM standards, engineering decomposition standards, and modeling software, an appropriate BIM platform and standard were selected to create BIM models for each component of cable-stayed bridges. Using the Yellow River Cable-stayed Bridge as a case study, various construction schemes were visualized through BIM. The study investigated the impact of key structural parameters, such as cable stiffness, main girder stiffness, and main tower stiffness, on the top push method by adjusting them by − 3%, − 1%, 1%, and 3%. The outcomes showed that changes in cable stiffness had the most significant effect, with a 1% stiffness variation causing a 51.3 mm displacement in the main girder and a 124.2 kN deviation in cable force, increasing to 151.2 mm and 179.8 kN respectively for a 3% change. This research demonstrates that BIM technology can significantly improve the management of top-push construction methods, enable three-dimensional visualization of the construction process, and advance the informatization and industrialization of bridge construction. Article Highlights The three-dimensional visualization and refined management of cable-stayed bridge construction have been achieved using BIM technology. Developed a grid simplification algorithm based on quadratic error measurement, significantly reducing the amount of BIM model data. The influence of key structural parameters on top pushing construction was studied through parameter adjustment.